THE C^*-ALGEBRA T_m AS A CROSSED PRODUCT - Hovsepyan, K.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
In this paper we consider the C^*-subalgebra T_m of the Toeplitz algebra T generated by monomials, which have an index divisible by m. We present the algebra T_m as a crossed product: T_m=φ(A)×_δ_mZ, where A=C_0(Z_+)CI is C^*-algebra of all continuous functions on Z_+, which have a finite limit at infinity. In the case m=1 we obtain that T=φ(A)×_δ_1Z, which is an analogue of Coburn’s theorem.